PENGELOLAAN DATA POTENSI DAN PELUANG INVESTASI PADA KAWASAN WISATA MANDEH BERBASIS SIG WEB - rahmat ilham 125; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine: 1) the process of designing and developing a potential data management system and investment opportunities in the sigweb-based Mandeh tourist area, 2) the quality of the system developed based on the standardization of quality assessment of websites and web applications from WEBQEM. This research was conducted using a research and development approach. In developing an information system, a development methodology is needed. The information system development methodology used in this study is the waterfall methodology. This type of research is classified as Mix Methods. Population The research subjects were 8 people consisting of heads of offices, secretaries, IT operators and 4 active investors in DPMPPTSP Pesisir Selatan Regency. The results of this study indicate that 1) The development process is carried out in several stages. The stages used are based on the steps of the research and development method according to Sugiyono. The steps in the research and development method according to Sugiyono consist of 10 steps, namely potentials and problems, data collection, product design, system validation, design revision, product testing, product revision, usage testing, product revision and mass production. System development produces a system that can manage potential data & investment opportunities and user data that can manage the system, 2) The system built has met the quality of the system based on the standardized quality assessment of the website and the WEBQM web application. This conclusion is based on the results of the system testing which includes testing functionality, usability, reliability and efficiency. The results of the functionality testing get a final value of 1 which indicates the system being built has good functionality and can function properly. The results of reliability testing using the LOADER.IO application produce a successful percentage of stress tests on a system that is loaded with 50 user traffic in 1 minute with a success rate of 50 and 0 failure with an average system response time of 376 ms / millisecond and it can be concluded that the system has met standards on the aspect of reliability. In the efficiency test, it produces an average value of 87.9 with an average grade of B and an average respond time of 1.5 seconds. Meanwhile, usability testing gets a percentage of 88% which indicates the system has met the standards in the usability aspect.